Peningkatan Keterampilan Membaca Pemahaman Melalui Model Pembelajaran RADEC (Read-Answer-Discuss-Explain and Create) Pada Siswa Kelas V SD Inpres 33 Ambon - Lekatompessy, Yulia Melissa; Notanubun, Zainudin; Ririhena, Ribka L. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the level of reading comprehension skills through the RADEC (Read-Answer-Discuss-Explain and Create) learning model in fifth-grade students at SD Inpres 33 Ambon. This study uses a classroom action research (CAR) design with 18 fifth-grade students at SD Inpres 33 Ambon as the research subjects. The results of the study indicate that reading comprehension learning through the RADEC (Read-Answer-Discuss-Explain and Create) learning model can improve the reading comprehension skills of fifth-grade students at SD Inpres 33 Ambon.